2012
DOI: 10.1007/s00216-012-6016-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional flow magnetophoresis of microparticles

Abstract: A new two-dimensional micro-flow magnetophoresis device was constructed in a superconducting magnet (10 T) using triangular shaped pole pieces, which could apply a magnetic strength, B(dB/dx), in the range of ca. 0-14,000 T(2) m(-1) across a capillary cell. Polystyrene particles with diameters of 1, 3, and 6 μm were used as test samples in a paramagnetic medium of 1 M MnCl(2) to evaluate the performance of this method. Microparticles migrated across the capillary along the edge of the pole pieces, and then flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Reproduced from ref. [59] (c) Deflection of diamagnetic particles by a permanent magnet in a microfluidic system. Reproduced from ref.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced from ref. [59] (c) Deflection of diamagnetic particles by a permanent magnet in a microfluidic system. Reproduced from ref.…”
Section: Figurementioning
confidence: 99%
“…Tarn et al [ 51 ] applied diamagnetophoresis for a continuous separation of diamagnetic particles in MnCl 2 solution (0.48 and 0.79 M ), as shown in Figure 3 a. They examined the separation of 5 μm and 10 μm diameter particles in different concentrations of this salt solution and concluded that better separation performance could be achieved with a higher concentration of MnCl 2 solution in a superconducting magnet with an external magnetic fl ux of 10 T. Kawano et al [ 59 ] developed a two-dimensional capillary cell to separate particles in MnCl 2 solution (1 M ) using triangular shaped pole pieces, as shown in Figure 3 b. Fractionation of particles with different diameters (1, 3, and 6 μm) was achieved in a superconducting magnet. They also fractionated deoxygenated and nondeoxygenated red blood cells using a wider capillary cell.…”
Section: Paramagnetic Salt Solution Based Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Faraday's ponderomotive method is preferable in a case of statement of the problem about determining a sample' s magnetic susceptibility χ with a small volume V. Herewith it could be both solid and disperse sample (for example, powder sample of ferro-or ferromagnetic particles, which are disperse phase of many technological mediums, including those which are affected by magnetophoresis and magnetic control [1][2][3][4][5][6]). A magnetic (ponderomotive) force F, acting on study "microsample", becomes basic measurement value when magnetic loop of Faraday balance of field with intensity H (induction B = μ 0 H) and nonuniformity gradH (gradB) is creating between pole pieces.…”
Section: Introductionmentioning
confidence: 99%
“…We are talking about the advancing applied scientific research in magnetophoresis and magnetic control of highly dispersed ferro-or ferrimagnetic particles (ferrofractions of many technological, natural and industry-specific media) [1][2][3][4][5][6], where one of the key issues is to obtain the data on the particles magnetic susceptibility. So, by the yielded (almost direct) results of the susceptibility of the sample represented by a conglomerate of the particles experimentally separated from some medium and necessary to realise the Faraday method, we can quite definitely estimate the susceptibility of single particles by dividing these data by the values of their packaging bulk density (under condition of their sufficient mutual separation).…”
Section: Introductionmentioning
confidence: 99%